PELUANG DAN TANTANGAN PENDIDIKAN MUHAMMADIYAH DI ERA 4.0 - Al Faruq, Umar (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This research article discusses the opportunities and challenges of Muhammadiyah education in the 4.0 Era. In this research researchers used a qualitative approach with the type of research libraries. The sources used are research journals, articles, books and other related information that can support data from this research. The results of the study are Muhammadiyah education has many chances to be able to compete because 1. It carries Tajdid movement or renewal, 2. In the direction of Indonesia and UUD 1945, 3. Relevant to the demands of the times, 4. It has a strong network both nationally and internationally. The strongest challenge faced by Muhammadiyah is the technology that is the fundamental core of the changes in the disruption era in the 4.0 industry.